Infantile Neuroaxonal Dystrophy: Diagnosis and Possible Treatments - Babin, Patricia L.; Rao, Sudheendra N. R.; Chacko, Anita; Alvina, Fidelia B.; Panwala, Anil; Panwala, Leena; Fumagalli, Danielle C. (Frontiers in Genetics, 2018)
Infantile Neuroaxonal Dystrophy (INAD) is a rare neurodegenerative disease that often cuts short the life span of a child to ten years. With a typical onset at six months of age, INAD is characterized by regression of acquired motor skills, delayed motor coordination and eventual loss of voluntary muscle control. Mutations in the PLA2G6 gene have been identified as the most frequent cause of INAD. We highlight the salient features of INAD molecular pathology and the progress made in molecular diagnostics. We reiterate that enhanced molecular diagnostic methodologies such as exome sequencing and whole gene sequencing can help ascertain a molecular diagnosis. We describe how the defective catalytic activity of the PLA2G6 gene could be potentially overcome by enzyme replacement or gene correction, giving examples and challenges specific to INAD. This is expected to encourage steps towards developing and testing emerging therapies that might alleviate INAD progression and help realize objectives of patient formed organizations such as the INADcure Foundation.